Indications for Digital Monitoring of Patients With Multiple Nevi: Recommendations from the International Dermoscopy Society - Teresa Russo; Vincenzo Piccolo; Elvira Moscarella; Philipp Tschandl; Harald Kittler; John Paoli; Aimilios Lallas; Ralph P Braun; Luc Thomas; H Peter Soyer; Josep Malvehy; Susana Puig; et al. (Dermatology Practical & Conceptual, 2022)
Introduction: In patients with multiple nevi, sequential imaging using total body skin photography (TBSP) coupled with digital dermoscopy (DD) documentation reduces unnecessary excisions and improves the early detection of melanoma. Correct patient selection is essential for optimizing the efficacy of this diagnostic approach.